2022
DOI: 10.1126/sciadv.abl9404
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of nanosilicates induces downstream endochondral differentiation gene expression program

Abstract: Bioactive materials harness the body’s innate regenerative potential by directing endogenous progenitor cells to facilitate tissue repair. Dissolution products of inorganic biomaterials provide unique biomolecular signaling for tissue-specific differentiation. Inorganic ions (minerals) are vital to biological processes and play crucial roles in regulating gene expression patterns and directing cellular fate. However, mechanisms by which ionic dissolution products affect cellular differentiation are not well ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Several studies claim IC50 values of Laponite vary considerably, ranging from 0.05 to 50 mg/mL [ 44 ]. Laponite particles have been shown to naturally degrade in ∼30 days on average; a hydrogel with a residence time of >30 days prevents complete Laponite particles escaping the hydrogel, thereby preventing adverse cytotoxicity [ 45 ]. Laponite, especially LaponiteⓇ XLG, is considered suitable for biomedical application due to its low heavy metal content.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies claim IC50 values of Laponite vary considerably, ranging from 0.05 to 50 mg/mL [ 44 ]. Laponite particles have been shown to naturally degrade in ∼30 days on average; a hydrogel with a residence time of >30 days prevents complete Laponite particles escaping the hydrogel, thereby preventing adverse cytotoxicity [ 45 ]. Laponite, especially LaponiteⓇ XLG, is considered suitable for biomedical application due to its low heavy metal content.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Brokesh et al reported the vulnerability of nanoclay particles for degradation at both pH 7.4 (mimicking extracellular environment) and pH 5.5 (mimicking endosome microenvironment) in a time-dependent manner. 44 Moreover, anticancer drugs loaded on/in nanoclay followed higher release rate in acidic lysosomal-mimicking pH conditions than in physiological conditions 32,45 which might again be attributed to acid-enhanced nanoparticle degradation under these low pH conditions. The equation for this pH dependent dissolution is shown by Thompson and Butterworth equation below.…”
Section: Discussion and Analysismentioning
confidence: 95%
“…Interestingly, when BAG fillers were added at a concentration of 7.7 vol%, ALP expression increased dramatically, while it still remained lower than the control group. A study [27] demonstrated that higher concentrations of Si induced higher differentiationrelated gene expression upregulation. The higher release of Si in BAG7.7 than in BAG1.9 and BAG3.8 might account for the increased ALP activity, which was still lower than that of the control group without BAG fillers due to the adverse effects of the alkaline environment.…”
Section: Effects Of Bag Fillers On the Cellular Activity Of Dental Re...mentioning
confidence: 99%